Father Brown. Season 1 [videorecording (DVD)]. - Chesterton, G. K. (Gilbert Keith), 1874-1936; Barber, Ian (Television director); Cusack, Sorcha, 1949-; Speer, Hugo; Williams, Mark, 1959- (BBC Worldwide, 2013)
Celebrated author GK Chesterton's beloved character, Father Brown, is brilliantly brought to life in this charming ten-part BBC series starring Mark Williams (Harry Potter, Doctor Who). With the warmth of The Vicar of Dibley, the intellect of Miss Marple, the humour of Father Ted and the intrigue of Sherlock Holmes, Father Brown is a fresh new take on a classic genre. Set in the 1950s in the heart of the English countryside, Father Brown is a kindly cleric with a particular talent for solving crimes. Many years spent hearing confessions have given him an uncanny insight into the workings of the criminal mind, and in each episode the enigmatic priest discovers the truth of a crime by looking into the truth of the soul, the passions, dark secrets, hidden desires.